Development and validation of the Alimetry Gut-Brain Wellbeing Survey: a novel patient-reported mental health scale for patients with chronic gastroduodenal symptoms - Law, Mikaela; Pickering, Isabella; Humphrey, Gayl; Sebaratnam, Gabrielle; Schamberg, Gabriel; Simpson, Katie; Varghese, Chris; Du, Peng; Daker, Charlotte; Huang, I-Hsuan; Khalsa, Sahib S.; Gharibans, Armen; et al. (Frontiers in Psychology, 2024)
Objective: There is currently a lack of validated questionnaires designed specifically to assess mental health within patients with chronic gastroduodenal symptoms. This research describes the multi-phase process used to develop and validate a novel mental health scale for patients with chronic gastroduodenal symptoms, the Alimetry® Gut-Brain Wellbeing (AGBW) Survey. Methods: A patient-centred multi-phase process was implemented. In Phase 1, the most relevant concepts for this patient population were selected from existing mental health scales, using data from 79 patients. In Phase 2, an interdisciplinary panel of experts generated scale items. In Phase 3, the scale underwent pre-testing with gastroenterologists (n=9), health psychologists (n=3), and patients (n=12), with feedback incorporated over multiple rounds. Lastly, the psychometric properties of the scale were assessed in a sample of 311 patients via an online survey.The AGBW Survey comprises a patient preface, 10 close-ended questions, and an optional open-ended question. This multidimensional scale assesses general mental health, alongside specific subscales relating to depression, stress, and anxiety. The subscale and total scores demonstrated high internal consistency (α= .91 for the total scale; α= .72-.86 for subscales) and good convergent, divergent, concurrent validity, and known groups validity, with large effect sizes.The AGBW Survey is a brief, valid, and reliable scale for assessing mental health in patients with chronic gastroduodenal symptoms. It can be used as a tool to complement physiological tests and has the potential to guide psychological referrals, inform multidisciplinary management, and evaluate treatment outcomes.